1998
DOI: 10.1046/j.1365-2052.1998.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genetic variability of 23 bovine microsatellite markers in four Belgian cattle breeds

Abstract: The polymorphism of 23 microsatellites in the four main cattle breeds in Belgium (Holstein Friesian, Belgian Blue, Belgian Red Pied and East Flemish) was analysed. Heterozygosity, polymorphism information content, the effective number of alleles, exclusion probability and the probability of genotypic identity for two random individuals were calculated for all microsatellites and all breeds. The Belgian Blue breed is generally a little less polymorphic in comparison with the other three breeds. Estimates of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
1
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 4 publications
7
16
1
3
Order By: Relevance
“…According to Peelman et al (1998), who analyzed Belgium cattle, the number of TGLA53 locus alleles in Holstein Friesian (13 alleles), Belgian Red Pied (12 alleles), East Flemish (12 alleles) and Belgian Blue (10 alleles) cattle were very similar to that found in Nellore cattle (13 alleles). However, we found that the exclusion probability for the TGLA53 locus in Brazilian Nellore (EP = 0.256) cattle is much lower than in the four Belgian breeds (Holstein Friesian = 0.742, Belgian Red Pied = 0.711, East Flemish = 0.698 and Belgian Blue = 0.682).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to Peelman et al (1998), who analyzed Belgium cattle, the number of TGLA53 locus alleles in Holstein Friesian (13 alleles), Belgian Red Pied (12 alleles), East Flemish (12 alleles) and Belgian Blue (10 alleles) cattle were very similar to that found in Nellore cattle (13 alleles). However, we found that the exclusion probability for the TGLA53 locus in Brazilian Nellore (EP = 0.256) cattle is much lower than in the four Belgian breeds (Holstein Friesian = 0.742, Belgian Red Pied = 0.711, East Flemish = 0.698 and Belgian Blue = 0.682).…”
Section: Discussionmentioning
confidence: 92%
“…The exclusion probability values for the TGLA227, ETH10 and TGLA53 loci of taurine cattle described by Peelman et al (1998) and Heyen et al (1997) are much higher than that of Nellore cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2002), evaluating genetic diversity based on 13 microsatellites using DA distance and N-J tree, found the group of Chinese and Korean cattle, the Japanese Black cattle was clearly distinct. Microsatellites are commonly held to be sufficient for the explanation of evolutionary relationships (Takezaki and Nei, 1996;Basedow, 1998;Peelman et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…따라서 분자유전학적 유전표 지를 근거로 한 계통 분류는 품종 식별, 개체 식별 및 외래품 종간 차별성 제공 등을 통하여 한국 재래닭의 유전자원으로서 의 활용 측면에서 매우 유용한 정보를 제공할 수 있을 것으 로 생각된다. Microsatellite(MS) marker는 유전적 다양성이 높 고 동물 게놈 전반에 걸쳐 분포한다는 특성을 가지고 있어 집 단 내 또는 집단 간 유전적 유연관계 및 다양성을 추정하는 데 널리 활용되고 있다 (Buchanan et al, 1994;Barker et al, 1997;Peelman et al, 1998;Martin et al, 1999;Li et al, 2000;Bjornstad et al, 2003). MS marker의 유전다형 형태를 분석하 는 일련의 유전자 감식 방법이 개체 식별의 강력한 수단으 로 제공되고 있어 현재 가장 보편화된 분석 방법으로 채택 되고 있다 (Fries and Durstewitz, 2001;Sancrostoval et al, 2000;Vignal et al, 2002 는 Nei(1972는 Nei( , 1978 population based on DA genetic distance (Nei et.…”
Section: 서 론unclassified